2020
DOI: 10.1093/brain/awaa176
|View full text |Cite|
|
Sign up to set email alerts
|

SLC12A2 variants cause a neurodevelopmental disorder or cochleovestibular defect

Abstract: The SLC12 gene family consists of SLC12A1–SLC12A9, encoding electroneutral cation-coupled chloride co-transporters. SCL12A2 has been shown to play a role in corticogenesis and therefore represents a strong candidate neurodevelopmental disorder gene. Through trio exome sequencing we identified de novo mutations in SLC12A2 in six children with neurodevelopmental disorders. All had developmental delay or intellectual disability ranging from mild to severe. Two had sensorineural deafness. We also identified SLC12A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…The NKCC1-deficient patient also had severe hearing loss, cochlear defects, and abnormal auditory brainstem responses (ABRs). Several patients with missense mutations in NKCC1, rather than complete loss-of-function mutations, display bilateral sensorineural hearing loss ( McNeill et al, 2020 ). NGLY1 deficiency patients do not have severe hearing loss, but do report abnormal ABRs.…”
Section: Discussionmentioning
confidence: 99%
“…The NKCC1-deficient patient also had severe hearing loss, cochlear defects, and abnormal auditory brainstem responses (ABRs). Several patients with missense mutations in NKCC1, rather than complete loss-of-function mutations, display bilateral sensorineural hearing loss ( McNeill et al, 2020 ). NGLY1 deficiency patients do not have severe hearing loss, but do report abnormal ABRs.…”
Section: Discussionmentioning
confidence: 99%
“…Because her fibroblasts were collected, genetic analysis revealed that she carried both her parent's mutations. Evidence is now mounting that de novo (single allele) mutations lead to neurodevelopmental deficits and cochlea-vestibular defects (McNeill et al, 2020;Mutai et al, 2020). Another patient with NKCC1 mutation deserves some attention in the context of this review article.…”
Section: Na + /Glucose Transporter (Sglt)mentioning
confidence: 99%
“…In a second study, we identified three individuals from two independent families with mutations in exon 21 associated with nonsyndromic bilateral sensorineural deafness ( Table 2 ). 99 In the first family, a 2-year-old boy had a p.Glu980Lys mutation, and in the second family, a 44-year-old father and his 5-year-old son carried a mutation of the preceding residue (p.Glu979Lys). Note that two additional patients with mutations in other parts of the transporter (p.Ala327Val and p.Trp892*) also demonstrated bilateral sensorineural hearing impairment.…”
Section: Slc12a2 Haplotype Insufficiency and Hearing Lossmentioning
confidence: 99%
“…Note that two additional patients with mutations in other parts of the transporter (p.Ala327Val and p.Trp892*) also demonstrated bilateral sensorineural hearing impairment. 99 …”
Section: Slc12a2 Haplotype Insufficiency and Hearing Lossmentioning
confidence: 99%